2021
DOI: 10.1002/suco.202000821
|View full text |Cite
|
Sign up to set email alerts
|

Residual mechanical properties of concrete containing lightweight expanded clay aggregate (LECA) after exposure to elevated temperatures

Abstract: The mechanical properties of light-weight concrete (LWC) in fire are known to be better than those of normal-strength concrete (NSC), both at high temperature (hot properties) and after cooling (residual properties). The objective of this paper is to increase the knowledge of LWC's residual properties by testing a number of mixes containing expanded clay as light-weight coarse aggregate.An experimental program was carried out, in which one normal-weight concrete mix and two lightweight aggregate mixes containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Other authors (Rashad, 2018;Yew et al, 2020;Ahmad and Chen, 2019;Hubertova and Hela, 2013) reported that increasing the substitution rate of ECA decreases the compressive strength of concrete by up to 20%. It was also reported (Yew et al, 2020;Bogas et al, 2012;Chidighikaobi, 2019;Dabbaghi et al, 2021;Dilli et al, 2015;Nahhab and Ketab, 2020) that the use of ECA decreases flexural strength, splitting tensile strength and modulus of elasticity which generate more brittle behavior compared to conventional concrete. Research by Yew et al (2020) and Nahhab and Ketab (2020) suggested that a clay aggregate substitution rate of 60-70% is considered optimal with a maximum size of 10 mm.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other authors (Rashad, 2018;Yew et al, 2020;Ahmad and Chen, 2019;Hubertova and Hela, 2013) reported that increasing the substitution rate of ECA decreases the compressive strength of concrete by up to 20%. It was also reported (Yew et al, 2020;Bogas et al, 2012;Chidighikaobi, 2019;Dabbaghi et al, 2021;Dilli et al, 2015;Nahhab and Ketab, 2020) that the use of ECA decreases flexural strength, splitting tensile strength and modulus of elasticity which generate more brittle behavior compared to conventional concrete. Research by Yew et al (2020) and Nahhab and Ketab (2020) suggested that a clay aggregate substitution rate of 60-70% is considered optimal with a maximum size of 10 mm.…”
Section: Introductionmentioning
confidence: 91%
“…The open and closed pores of ECA, also, contribute to improving the properties of concrete against chloride penetration and reinforcement corrosion. Other authors, i.e., Chidighikaobi (2019), Dabbaghi et al, (2021), Ismail and Halim (2020), and Uglyanitsa et al, (2015), demonstrated that mixtures with ECA have higher thermal insulation and less affected than ordinary concrete after exposure to high temperatures or after cooling, which is favorable to improving the energy consumption of buildings. Several studies (Nahhab and Ketab, 2020;Nepomuceno, 2018;Ismail and Halim, 2020;Muñoz et al, 2018) found that the properties of mortars and concretes containing ECA depend on the size and shape of aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, no sharp drop in strength is experienced in concrete at temperatures below 300 C and the strength can be partially restored through rehydration. [8][9][10][11][12] However, concrete strength is severely degraded and cannot be restored at temperatures exceeding 300 C. 34 The fire resistance of LWC is superior to that of ordinary concrete owing to the porous network in lightweight aggregates and the egress of steam pressure during the heating process through the porous network of lightweight aggregates, which mitigates damage. 35 Researchers have explored the mechanical properties of LWC after heating.…”
Section: Effect Of Fire On Lightweight Concretementioning
confidence: 99%
“…10 On the other hand, LECA incorporation significantly improves the fire resistance due to the high temperature (1200°C) exposure during its production stage and lower thermal expansion, 11 and presence of pores (reduce steam pressure). 12 It was reported that the optimal level of LECA replacement was defined by minimizing the economic cost and environmental life cycle, while maximizing the compressive and tensile strengths. The cost increases with increasing strength, environmental life cycle and LECA replacement.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, there are a few research studies investigating the effect of lightweight expanded clay aggregates (LECA) on the mechanical strengths of lightweight Ordinary Portland cement or geopolymer mortars without using fibers, 12, 24, 25 and most of these studies apply heat-curing, which is difficult on-site applications. In literature, there is no study found on the influence of PVA fibers on the mechanical strength of LECA containing geopolymer mortars cured at an ambient temperature.…”
Section: Introductionmentioning
confidence: 99%